Molecular Analysis of a Short-term Model of β-Glucans-Trained Immunity Highlights the Accessory Contribution of GM-CSF in Priming Mouse Macrophages Response - Walachowski, Sarah; Tabouret, Guillaume; Fabre, Marion; Foucras, Gilles (Frontiers in Immunology, 2017)
β-glucans are glucose polymers present in the fungal cell wall and, as such, are recognized by innate immune cells as microbial-associated pattern through Dectin-1 receptor. Recent studies have highlighted the ability of the pathogenic yeast Candida albicans or its cell wall-derived β(1,3) (1,6)-glucans to increase human monocytes cytokine secretion upon secondary stimulation, a phenomenon now referred as immune training. This ability of monocytes programming confers β-glucans an undeniable immunotherapeutic potential. Our objective was to determine whether β-glucans from S. cerevisiae, a non-pathogenic yeast, are endowed with such a property. For this purpose we have developed a short-term training model based on LPS re-stimulation of mouse bone marrow-derived macrophages primed with S. cerevisiae β-glucans. Through a transcriptome analysis, we demonstrated that β-glucans induced a specific gene expression signature involving the PI3K/AKT signaling pathway as in human monocytes. Moreover, we showed that over-expression of Csf2 (that encodes for GM-CSF) was a Dectin-1-dependent feature of β-glucans-induced priming of macrophages. Further experiments confirmed that GM-CSF up-regulated Dectin-1 cell surface expression and amplified macrophages response along β-glucans-mediated training. However, the blockade of GM-CSFR demonstrated that GM-CSF was not primarily required for β-glucans-induced training of macrophages although it can substantially improve it. In addition, we found that mouse macrophages trained with β-glucans up-regulated their expression of the four and a half LIM-only protein 2 (Fhl2) in a Dectin-1-dependent manner. Consistently, we observed that intracellular levels of FHL2 increased after stimulation of macrophages with β-glucans. In conclusion, our experiments provide new insights on GM-CSF contribution to the training of cells from the monocytic lineage and highlights FHL2 as a possible regulator of β-glucans associated signaling.